Another morphogenetic movement on the map: Charting dorsal intercalation in C. elegans. Issue 2 (2nd April 2016) - Walck-Shannon, Elise; Hardin, Jeff
ABSTRACT: Dorsal intercalation is a coordinated cell migration event that rearranges hypodermal cells during C. elegans embryogenesis, and that resembles cell intercalation in many systems from flies to mice. Despite its conservation, the molecular mechanisms that govern dorsal intercalation in worms have remained elusive. Here, we comment on our recent publication, Walck-Shannon et al ., 1 which begins to spatially map the molecular requirements for intercalation. First, we provide a historical perspective on the factors that have previously hampered the study of dorsal intercalation. Next, we provide a summary of the molecular pathways identified in Walck-Shannon et al., 1 pointing out surprises along the way. Finally, we consider the potential conservation of the molecular pathway we described and discuss future questions surrounding dorsal intercalation. Despite the challenges, dorsal intercalation is a process poised to advance our understanding of cell intercalation during morphogenesis throughout the animal kingdom.